Measuring E-Customer Loyalty as an Implementation of Netflix’s Marketing Strategy - Gwigon, Kim; Pidada, Ida Ayu Iswari; Aryana, I Putu Yogi (Universitas Pendidikan Nasional, 2024)
This study examines Netflix’s performance in Indonesia, where it lags behind competitors and faces persistent negative feedback. Focusing on Netflix users in Denpasar, the research investigates how e-service quality and perceived value influence e-customer loyalty, with e-customer satisfaction as a mediating variable. Data were collected via a 17-item questionnaire and analyzed using Partial Least Squares (PLS). The results reveal that both e-service quality and perceived value significantly enhance e-customer satisfaction. However, only perceived value has a direct and indirect (mediated by satisfaction) impact on loyalty, whereas e-service quality shows no significant effect on loyalty, either directly or through mediation. These findings underscore the critical role of perceived value—such as cost-benefit trade-offs and content relevance—in fostering customer retention, while suggesting that service quality alone is insufficient to drive loyalty in this context. This study contributes to digital marketing strategy by emphasizing the need for platforms like Netflix to prioritize value perception over mere service efficiency in competitive markets. Future research could expand on these insights by exploring additional factors like e-recovery service quality, e-CRM, and e-trust, or by applying alternative theoretical frameworks in different regional or industry contexts.